EFL Learners’ Speaking Anxiety in an EOP Program - Irawan, Rifki (Journal of ELT Research, 2018)
This research aimed at describing students’ speaking anxiety in EFL classroom at occupation level. It investigated EOP students’ speaking anxiety levels, their sources of anxiety and their coping strategies to reduce it. This research involved eight students from two classes with different English abilities and employed a qualitative research design, embracing the characteristics of a case study conducted in PT Rekacipta Miratama Bekasi from December 2016 to March 2017. Three kinds of instruments were applied for this research: classroom observation, questionnaires (adapted from Foreign Language Classroom Anxiety Scale by Horwitz), and semi-structured interview. The data were collected by means audio and video recording to capture students’ sources of anxiety and their coping strategies and collaborated with a semi-structured interview. Those data were transcribed and coded by using the categorization from Alwasilahs’ coding strategy (2002) and obtained by quantifying questionnaires in order to know the students’ anxiety levels. The first finding reveals that the students who categorized as an anxious and a mildly anxious level had the highest percentage (each of them was 37%), while those who categorized as a relaxed and a very relaxed level had the lower of percentage (each of them was 17%). Secondly, the research participants who categorized as an anxious and a mildly anxious level stated that all FLA sources that are a communication apprehension, a test anxiety, and a fear of negative evaluation had similar percentages (each of them 33.34%). Lastly, coping strategies that all anxious students used in this research were anticipation that belonged to compromise behaviors.    Keywords: Speaking Anxiety, Anxiety Levels, Anxiety Sources, Coping Strategies to Reduce FLA, EOP Students